An observational case control study: study of preterm labour- risk factors and its outcome - Shah, Krima V.; Agrawal, Rushabh H.; Parmar, Radhika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Preterm birth is considered as the most significant risk in infant morbidity and mortality. The number of preterm births can be reduced significantly if all of the risk factors for predicting preterm births were eliminated to maximum extent. The aim of this study was analysis of risk factors of preterm labour and its outcome through case control study. Methods: It was an observational case control study of 200 pregnant women divided into study group of 100 pregnant women who were admitted with signs and symptoms of preterm labour with gestational age between 28-36 weeks. Control group of 100 pregnant women having gestational age above 36 weeks and with spontaneous onset of active labour. Risk factors and other parameters of both the groups were analyzed along with their neonatal outcome. Results: It was found that premature rupture of membrane, previous abortion, previous preterm delivery, anemia and impaired body mass index (BMI) are significantly higher in cases with preterm labour (p value <0.05). Hyperbilirubinemia, birth asphyxia and respiratory distress syndrome are significantly higher in cases with preterm labour (p value <0.05). Conclusions: Preterm labour is a multifactorial problem. Preterm labour and delivery require early and prolonged hospitalization causing great financial and psychological burden on the society and the number of preterm births can be reduced significantly if all of the risk factors for predicting preterm births were eliminated to maximum extent.